2016
DOI: 10.1016/j.jclinepi.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

ROBIS: A new tool to assess risk of bias in systematic reviews was developed

Abstract: ObjectiveTo develop ROBIS, a new tool for assessing the risk of bias in systematic reviews (rather than in primary studies).Study Design and SettingWe used four-stage approach to develop ROBIS: define the scope, review the evidence base, hold a face-to-face meeting, and refine the tool through piloting.ResultsROBIS is currently aimed at four broad categories of reviews mainly within health care settings: interventions, diagnosis, prognosis, and etiology. The target audience of ROBIS is primarily guideline deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1,299
0
42

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,486 publications
(1,344 citation statements)
references
References 19 publications
(19 reference statements)
3
1,299
0
42
Order By: Relevance
“…85 A second more recent tool is ROBIS, Risk of Bias in Systematic Reviews, which was released in 2015. 86 ROBIS focuses on risk of bias as opposed to the rigor of the process of a systematic review, which is the focus of AMSTAR. 87 In addition to the above tools, there are at least two reporting guidelines for systematic reviews: Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and Meta-analysis of Observational Studies in Epidemiology (MOOSE).…”
Section: Assessing the Credibility Of Existing Systematic Reviewsmentioning
confidence: 99%
“…85 A second more recent tool is ROBIS, Risk of Bias in Systematic Reviews, which was released in 2015. 86 ROBIS focuses on risk of bias as opposed to the rigor of the process of a systematic review, which is the focus of AMSTAR. 87 In addition to the above tools, there are at least two reporting guidelines for systematic reviews: Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and Meta-analysis of Observational Studies in Epidemiology (MOOSE).…”
Section: Assessing the Credibility Of Existing Systematic Reviewsmentioning
confidence: 99%
“…This stance reflects the raison d’être of the Cochrane Collaboration, whose use of explicit and auditable quality criteria for undertaking systematic reviews has inspired a weighty methodological handbook,3 numerous tools and checklists4, 5 and structured reporting criteria 6. There is strong emphasis on methodological reproducibility, with the implication that a different review team, using the same search criteria, quality checklists and synthesis tools, should obtain the same result 3…”
Section: Introductionmentioning
confidence: 99%
“…15 Finally, we assessed the risk of bias of the included systematic reviews with the newly-designed ROBIS tool. 16 From each eligible meta-analysis, the same two authors abstracted information independently on first author, year of publication, outcome examined, number of included studies, and reported data at the individual trial level. For each of the included studies in each eligible meta-analysis, we recorded the study design (RCT or non-RCT), the number of cases (for binary outcomes) and population participants.…”
Section: Eligibility Criteria and Data Extractionmentioning
confidence: 99%